An LC–MS/MS method for quantification of HR011303, a novel highly selective urate transporter 1 inhibitor in beagle dogs and the application to a pharmacokinetic study. (24th June 2019) - Wang, Ju; Yao, Wei; Fan, Di; Qiu, Zhenjun; Song, Jieqiong; Pan, Kai; Hang, Taijun
Abstract: HR011303 is a novel and highly selective urate transporter 1 (URAT1) inhibitor. In this study, a sensitive liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was developed and validated for quantification of HR011303 in beagle dog plasma. Plasma samples were pretreated with protein‐precipitation extraction by acetonitrile and added with a trifluoromethyl substituted analog of HR011303 as internal standard. The chromatographic separation was performed on a Shiseido C18 column (100 × 4.6 mm, i.d., 5 μm) by mobile phases consisting of 5 mm ammonium–formic acid (100:0.1) and acetonitrile–formic acid (100:0.1) solutions in gradient elution. The MS detection was conducted in electrospray positive ionization with multiple reactions monitoring at m / z 338 → 240 for HR011303 and m / z 328 → 230 for the internal standard using 25 eV argon gas collision induced dissociation. The established LC–MS/MS method showed good selectivity, sensitivity, precision and accuracy. The plasma pharmacokinetics of HR011303 in beagle dogs following both oral and intravenous administration were then successfully evaluated using this LC–MS/MS method.